ANALISIS PEMANFAATAN MEDIA PEMBELAJARAN DALAM MENGATASI KEJENUHAN BELAJAR SISWA DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM DI KELAS IV SD SWASTA ARISA MEDAN DELI TAHUN AJARAN 2022/2023 - Annisa Arnun (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2022)
Abstract: In science learning, low student learning achievement is caused by negative factors that reduce the motivation and enthusiasm for learning of grade IV students of SD Swasta Arisa Medan Deli School Year 2022/2023, especially in student psychological factors. The negative factor observed in this study is that student learning saturation results in low achievement in science learning subjects. The study was conducted to determine the factors causing learning saturation experienced by grade IV elementary school students. This research is a descriptive qualitative research. The subjects in this study were grade IV elementary school students who numbered 30 students and those who experienced learning saturation, namely students who had KKM scores that did not meet the number of 20 students. Data collection in this study was carried out by interviews, observations and documentation. Based on the results of research and discussions that have been presented about the boredom of student learning in science learning subjects in grade IV SD Swasta Arisa Medan Deli School Year 2022/2023 shows that from the results of interviews and observations there are still many students who are not interested in learning science because students have difficulty in understanding concepts, language difficulties and are not accompanied by supporting media, low student concentration, lack of study habits, low intelligence and lack of motivation given by parents, to overcome such things, teachers use concrete media to increase student motivation and morale. Keywodrs: low student learning achievement, learning saturation